Ethical Conundrums in Rural South Africa: Lost in Translation. (April 2017) - Teman, Eric D.; Richard, Veronica M.
We engage in story- re telling by recounting, reconstructing, and reflecting on our experiences as evaluators in a cross-cultural setting, a South African village. A principal focus on the serendipitous ethical and methodological issues that arose is highlighted. As most ethical dilemmas go, solutions are not clear. Therefore, the authors spend time critically considering the soundness of the decisions that were made, from the lack of diversity of the research team, to the ways we interacted with local citizens, to research design issues. We share our thoughts through a confessional tale via research poetry.